Sex and Estrous Cycle Effects on Anxiety- and Depression-Related Phenotypes in a Two-Hit Developmental Stress Model - Jaric, Ivana; Rocks, Devin; Cham, Heining; Herchek, Alice; Kundakovic, Marija (Frontiers in Molecular Neuroscience, 2019)
Stress during sensitive developmental periods can adversely affect physical and psychological development and contribute to later-life mental disorders. In particular, adverse experiences during childhood dramatically increase the risk for the development of depression and anxiety disorders. Although women of reproductive age are twice as likely to develop anxiety and depression than men of the corresponding age, little is known about sex-specific factors that promote or protect against the development of psychopathology. To examine potential developmental mechanisms driving sex disparity in risk for anxiety and depression, we established a two-hit developmental stress model including maternal separation in early life followed by social isolation in adolescence. Our study shows complex interactions between early-life and adolescent stress, between stress and sex, and between stress and female estrogen status in shaping behavioral phenotypes of adult animals. In general, increased locomotor activity and body weight reduction were the only two phenotypes where two stressors showed synergistic activity. In terms of anxiety- and depression-related phenotypes, single exposure to early-life stress had the most significant impact and was female-specific. We show that early-life stress disrupts the protective role of estrogen in females, and promotes female vulnerability to anxiety- and depression-related phenotypes associated with the low-estrogenic state. We found plausible transcriptional and epigenetic alterations in psychiatric risk genes, Nr3c1 and Cacna1c, that likely contributed to the stress-induced behavioral effects. In addition, two general transcriptional regulators, Egr1 and Dnmt1, were found to be dysregulated in maternally-separated females and in animals exposed to both stressors, respectively, providing insights into possible transcriptional mechanisms that underlie behavioral phenotypes. Our findings provide a novel insight into developmental risk factors and biological mechanisms driving sex differences in depression and anxiety disorders, facilitating the search for more effective, sex-specific treatments for these disorders.